Berotralstat in hereditary angioedema due to C1 inhibitor deficiency: first real-world evidence from a Canadian center - Srinivasan, Cindy; Ritchie, Bruce; Adatia, Adil (Frontiers in Immunology, 2024)
Background: Hereditary angioedema due to C1 inhibitor deficiency is a rare genetic condition that causes recurrent swelling with consequent functional impairment and decreased quality of life. Longterm prophylaxis (LTP) to prevent angioedema episodes is a key component of disease management. Berotralstat, an oral, once-daily plasma kallikrein inhibitor, was approved for LTP by Health Canada in 2022.Methods: We conducted a retrospective, real-world study investigating the effectiveness and adverse effects of berotralstat. Data on angioedema frequency, disease control, and adverse events were tabulated. Patient satisfaction with treatment was scored on a 5-point Likert scale, with 1 representing very unsatisfied and 5 representing very satisfied with therapy.Results: From June, 2022 and May, 2023, 8 patients with HAE type 1 or type 2 received berotralstat. Effectiveness data were available for 7 patients who continued the drug for at least 3 months, 4 of whom switched to berotralstat from plasma-derived C1 inhibitor LTP. In these 7 patients, the average number of attacks per month decreased from 3.3 to 1.6 (p<0.05), representing a 52% reduction in attack frequency. Median angioedema control test score numerically improved from 8 to 13 (p=0.0781). Of the 8 patients who received berotralstat, 3 reported no adverse effects and 5 experienced gastrointestinal side effects, which were mild and transient in 3 and led to discontinuation in 1. Average treatment satisfaction was between satisfied and very satisfied at 4.3.Berotralstat is an effective agent for long-term prophylaxis in HAE. Most patients experienced no adverse effects or mild, transient gastrointestinal symptoms.